Interference of a weed community in the soybean crop in functions of sowing spacing - Vitorino, Hermeson; Silva Junior, Antonio Carlos; Gonçalves, Clebson; Martins, Dagoberto (Revista Ciência Agronômica, 2017)
The use of double row spacing on soybean crop is recent and consists of a new soybean production technology in Brazil and worldwide, so weed interference may be different in relation to single crop row. Thus, the objective of this work was to evaluate the weed interference in soybean crop in function of sowing spacing. The experimental design was randomized blocks and treatments were arranged in a factorial (2x16): two spacings, a double row spacing [(0.20 x 0.20m) x 0.67 m] and a conventional single row spacing (0.45 x 0.45m) and sixteen periods of weed management, being eight control periods in which soybean was kept free of weeds by increasing periods of 7; 14; 21; 28; 35; 42; 49 and 145 days after emergence and eight coexistence periods, when the crop was maintained in the presence of the weed community for the same periods. The Critical Timing of Weed Removal (CTWR) was lower in the double row spacing, with eight days, compared with single spacing that was of 18 days. The Critical Weed-Free Period (CWFP) was of 36 and 31 days for double and single row spacing, respectively, and the emergence of weeds after this period did not cause damage to the productivity, but the Critical Period of Weed Control (CPWC) was higher in double row spacing (28 days) compared to the single row, which was of 13 days. The spacing in double row had a higher grain yield than the spacing in single row.